Risk Stratification for the Rate and Location of Residual Bladder Tumor for the Decision of Re-Transurethral Resection of Bladder Tumor - Fan, Junjie; Zhang, Xing; Fan, Jinhai; Li, Lei; He, Dalin; Wu, Kaijie (Frontiers in Oncology, 2022)
Introduction: To assess the rate and location of residual tumour in re-transurethral resection of bladder tumour (re-TURBT) and develop a risk stratification tool to assist clinicians making treatment decisions. Patients and Methods: The data of 144 patients with high-risk bladder cancer who received re-TURBT were retrospectively reviewed. The rate and location of residual tumours were recorded. Logistic regression was performed to explore risk factors for residual tumour, and a risk classification tool was developed. Results: Among the 144 patients, the rates of residual tumour and tumour location at the base of the primary tumour were 22.2% and 10.4%, respectively. Non-urothelial carcinoma subspecialist, piecemeal resection and the absence of detrusor muscle in the first specimen were defined as risk factors. Patients were categorized into low-, intermediate- and high-risk groups according to the number of risk factors. The rate of residual tumour in the high-risk group was significantly higher than that in the low- and intermediate-risk groups (50% vs. 7.8%, P=0.001; 50% vs. 18.6%, P=0.002). Moreover, high-risk patients benefit more from second resection at the base of the primary tumour due to the high rate of residual tumour located at this site than low- and intermediate-risk patients (23.5% vs. 2.0%, P=0.002; 23.5% vs. 10.2%, P=0.083). Conclusions: Risk stratification based on the subspecialist category, operative method, and presence or absence of detrusor muscle in the first specimen could help identify patients who benefit from re-TURBT and second resection the base of the primary tumour.